Proceedings of the 30th International Symposium on Automation and Robotics in Construction and Mining (ISARC 2013): Building Th 2013
DOI: 10.22260/isarc2013/0010
|View full text |Cite
|
Sign up to set email alerts
|

Lean Method to Identify Improvements for Operation Control at Quarry Sites

Abstract: The operation of Quarry and Aggregate sites are similar to factory production, since it contains sequential production processes, tasks and activities to produce the output product. Compared to the plant though, the quarry processes are generally not synchronized and controlled towards the overall throughput of the site in real time. Some quarries control parts of the production but do generally not utilize real-time technologies for the whole site and all its activities. This fact indicates a general improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In [2], it was described that waiting can occur at loading and unloading by an average of 30% of the operating time for haulers. In Figure 4 the increase of travel time by 37% from 78 s at top speed to 107 s would decrease the fuel consumption from start to stop by nearly 25%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In [2], it was described that waiting can occur at loading and unloading by an average of 30% of the operating time for haulers. In Figure 4 the increase of travel time by 37% from 78 s at top speed to 107 s would decrease the fuel consumption from start to stop by nearly 25%.…”
Section: Discussionmentioning
confidence: 99%
“…The two test configurations did not show exactly the same results but the tendency is the same in terms of fuel savings of about 20-30% with increased travel time of between 30-37%. In [2] it was shown that quarry sites can have up to 30% wastes in waiting times and unnecessary stops. In addition, [8] shows that communication coverage can be obtained with wireless ad-hoc communication technologies between mobile machines in a quarry environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations